Bluebeard gothic : Jane Eyre and its progeny - Pyrhönen, Heta, 1960- (University of Toronto Press, 2010)
Using psychoanalysis as the primary model of textual analysis, Bluebeard Gothic focuses on the conjunction of religion, sacrifice, and scapegoating to provide an original interpretation of a canonical and frequently-studied text.